2021
DOI: 10.1108/jcom-10-2020-0107
|View full text |Cite
|
Sign up to set email alerts
|

Achieving employee support during the COVID-19 pandemic – the role of relational and informational crisis communication in Austrian organizations

Abstract: PurposeBased on social exchange theory, the study examines the influence of informational and relational internal communication on cognitive and affective responses and job engagement during organizational crises caused by the COVID-19 pandemic.Design/methodology/approachData were collected by means of an online survey among people working in organizations with a minimum of 10 employees (N = 1,033) and analyzed using structural equation modeling.FindingsResults show that informational and relational communicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0
21

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(126 citation statements)
references
References 80 publications
4
86
0
21
Order By: Relevance
“…In remote work situations like those faced during the Covid-19 pandemic, organizations needed to sustain employees engagement and maintain their ability to communicate, collaborate and function properly [ 62 ]. Therefore, there is a need for various engagement practices to help support employees working from home.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In remote work situations like those faced during the Covid-19 pandemic, organizations needed to sustain employees engagement and maintain their ability to communicate, collaborate and function properly [ 62 ]. Therefore, there is a need for various engagement practices to help support employees working from home.…”
Section: Discussionmentioning
confidence: 99%
“…For the evaluation stage, a case study approach was adopted to evaluate the proposed assessment method in a real context. The case study approach is defined as "a strategy for doing research which involves an empirical investigation of a particular contemporary phenomenon within its real-life context using multiple sources of evidence" [61].…”
Section: Evaluation Methodsmentioning
confidence: 99%
“…The global pandemic caused by SARS-CoV-2 virus (further called COVID-19 pandemic) had a profound impact on the management of employees [ 3 , 4 ]. Spread of the COVID-19 disease meant that organizations were forced to change the way of work, as it became necessary to increase the social distance and stop the mobility in order to reduce the odds of contamination [ 5 ]. Organizations had to rearrange their processes so that remote work was possible [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, in a study of 1033 employees in Austrian organizations during the COVID-19 pandemic, employees' satisfaction with factual corporate information (β=0.27, p < 0.001) enhances the acceptance of managerial decisions and, in turn, employees' acceptance of managerial decisions has a weak but significant relationship (β = 0.11, p < 0.05) with job engagement. Specifically, employees' acceptance of managerial decisions explained variance of R² = 0.44 on job engagement (Einwiller, Ruppel, & Stranzl, 2021). Equally, Tao et al (2021) confirmed a linkage between employees' needs satisfaction and organizational engagement.…”
Section: Covid-19 Individual Level Constructsmentioning
confidence: 67%
“…Receiving substantial information increases employees' acceptance of managerial decisions (β = 0.41, p < 0.001), and employees' acceptance of managerial decisions, in turn, stimulates employees' job engagement (β = 0.11, p < 0.05) in employees of Austrian organizations (Einwiller et al, 2021). In addition, during the COVID-19 crisis, Einwiller et al (2021) demonstrated that participation (β =0.16, p < 0.01) (listening to and receiving feedback from employees) and communicated appreciation (β=0.42, p < 0.001) boost affective organizational commitment while affective organizational commitment, in turn, drives employees' job engagement (β=0.57, p<0.001) in 1033 Austrian employees.…”
Section: Covid-19 Organizational Level Constructsmentioning
confidence: 99%